(untitled) - Grublova, Eva (Doprava a spoje, 2010)
The paper describes the possible ways how to support the raise of company's innovativeness using of social and psychological tools that influence employees' behavior in order to success in new global competition conditions. In order to apply these tools, managers must change their approach to the employees' assessment. Organization can establish strategic alliance to extend its innovation strategy.